PELATIHAN PENGELOLAAN KEUANGAN KELUARGA BAGI IBU-IBU PKK KELURAHAN PONDOK PUCUNG UNTUK MENJADI KELUARGA MANDIRI DAN SEJAHTERA - Krida Puji Rahayu (Rural Development For Economic Resilience (RUDENCE), 2023)
ABSTRACT The activity was carried out in the form of real activity and aimed to Give participants an understanding of its importance preparation of financial reports for PKK women and provide knowledge and training to participants on how to preparation of finances for PKK mothers, in the Pondok Pucung village. With the aim that management training family finances can go well-good and directed, then the method of implementation activities are designed in several stages activities include: 1) planning stage and preparation, 2) implementation stage, 3) final evaluation stage and 4) reporting. The activity results showed that the participants of this activity were satisfied with the simulation of making financial report directly and evaluated by the source person. Because it opened the minds of the participants. The results are very satisfying and visible from the enthusiasm of their participants enthusiasm and I am happy to take part in this community service program activity because related to their vital issues in this pandemic time. ABSTRAK Pengabdian ini berjudul Pelatihan Pengelolaan Keuangan Keluarga Bagi Ibu-Ibu PKK Kelurahan Pondok Pucung Untuk Menjadi Keluarga Mandiri dan Sejahtera. Dengan tujuan agar pelatihan pengelolaan keuangan keluarga dapat berjalan dengan baik dan terarah pada masa pandemi covid- 19, maka metode pelaksanaan kegiatan dirancang dalam beberapa tahapan kegiatan antara lain: 1) tahap perencanaan dan persiapan, 2) tahap pelaksanaan, 3) tahap evaluasi akhir dan 4) pelaporan. Hasil kegiatan menunjukkan bahwa peserta kegiatan ini merasa puas dengan simulasi pembuatan laporan keuangan secara langsung dan dievaluasi oleh narasumber. Oleh karena itu, kegiatan ini secara tidak langsung membuka pikiran para peserta. Hasilnya sangat memuaskan dan terlihat dari antusiasme para pesertanya dan saya senang mengikuti kegiatan program pengabdian masyarakat ini karena terkait dengan isu-isu vital mereka di masa pandemi ini.